Curriculum planning. The direct way. - ds Moura, J L; Ferreira, H G (Acta Médica Portuguesa, 1996)
An attempt is being made in several Portuguese Medical Schools to reduce the Medical Course to five academic years. It will be easier and much more rigorous to base these changes on a detailed list of Educational Objectives. The choice of Educational Objectives must take into account the professional and social context surrounding the non-specialist physician (family doctor, general practitioner, etc), the background and maturity of the students, the manpower and resources of the Medical School and the results of the evaluation of the medical graduates as they finish their undergraduate training. This paper is an attempt to produce a list of Educational Objectives for undergraduate training in urology. Since we lack adequate information in relation to Portugal, we relied on epidemiological data from other countries as well as the experience obtained in similar attempts carried out in the USA.